The Effect of Service Quality on Customer Retention and Customer Experience as Mediating Variable - Reza Suriansha; Ngadino Surip Diposumarto; Hari Muharam (West Science Business and Management, 2024)
The customer's role is crucial in business, including modern retail. Therefore, this research aims to discover ways to enhance customer retention in modern retail by exploring the impact of relationship quality and customer experience at Ramayana department stores. The study focuses on customers from Ramayana department stores in the DKI Jakarta region. Using proportional random sampling, a sample of 400 customers was selected. Path analysis with JASP software was used for data analysis. The research findings are: 1) Service quality has a significant and positive impact on Customer Experience at Ramayana Department Store. 2).Customer Experience significantly and positively influences Customer Retention at Ramayana Department Store. 3). Service quality positively impacts Customer Retention through Customer Experience as a full mediator at Ramayana Department Store.